TANGGUNG JAWAB KORPORASI FINTECH LENDING ILEGAL DALAM PERSPEKTIF PERLINDUNGAN KONSUMEN [Corporate Liability of Illegal Fintech Lending in the Perspective of Consumer Protection Law] - Suseno Adi Wibowo; Yeti Sumiyati (Law Review, 2021)
The complexity of fintech lending practice has resulted in two problems: first: the regulation of illegal fintech, and second: the corporate liability of illegal fintech lending in terms of consumer protection in the case of PT Vega Data Indonesia. This research uses normative judicial methods by analyzing the laws related to the practice of fintech lending and aimed at illegal fintech lending corporates. The research has found that: first, rules and regulations on illegal fintech lending corporate cannot be found in any Indonesian laws. There has been no sufficient rules and regulations to settle illegal fintech lending problems and this disadvantages consumers. Therefore, special regulations on illegal fintech lending corporation must be set up immediately. Second, both civil and penal liability were imposed on illegal fintech lending corporate PT Vega Data Indonesia through systematic legal interpretation method based on corporate criminal liability doctrine. It is expected that this research may contribute to the efforts to handle illegal fintech lending cases through corporate liability in order to support the attempts of legal protection for customers.Bahasa Indonesia Abstrak: Kompleksitas penyelenggaraan fintech lending menimbulkan permasalahan, yaitu: pertama, pengaturan korporasi fintech lending ilegal dalam hukum positif Indonesia. Kedua, tanggung jawab korporasi fintech lending ilegal dalam perspektif perlindungan konsumen pada kasus PT Vega Data Indonesia. Metode penelitian secara yuridis normatif dengan menganalisa peraturan perundang-undangan yang berkaitan penyelenggaraan fintech lending serta dihubungkan dengan kasus korporasi fintech lending ilegal. Hasil penelitian menyimpulkan: pertama, dalam hukum positif Indonesia tidak ada yang mengatur mengenai korporasi fintech lending ilegal. Aturan-aturan terkait fintech lending belum cukup mengakomodir dan menyelesaikan permasalahan penyelenggaraan fintech lending ilegal yang mengakibatkan lemahnya perlindungan terhadap konsumen, sehingga perlu pembentukan undang-undang secara khusus yang mengatur korporasi fintech lending ilegal. Kedua, selain tanggung jawab secara perdata, tanggung jawab pidana juga dibebankan kepada korporasi fintech lending ilegal PT Vega Data Indonesia melalui metode penafsiran hukum sistematis dan mengacu pada doktrin pertanggungjawaban pidana korporasi. Hasil penelitian ini diharapkan memberi kontribusi terhadap upaya penanganan perkara fintech lending ilegal melalui penerapan pertanggungjawaban pidana korporasi agar dapat memberikan perlindungan hukum yang berkeadilan bagi konsumen.